Preverbal infants' sensitivity to grammatical dependencies. (30th March 2022) - Babineau, Mireille; Christophe, Anne
Abstract: During their first months of life, infants can already distinguish function words (e.g., pronouns and determiners) from content words (e.g., verbs and nouns). Little research has explored preverbal infants' sensitivity to the relationships between these word categories. This preregistered study examines whether French‐learning 8‐ and 11‐month‐olds track the grammatical dependencies between determiners and nouns as well as pronouns and verbs. Using the Visual Fixation Procedure, infants were presented with lists containing either grammatical (e.g., tu manges "you eat", des biberons "some bottles") or ungrammatical (e.g., des manges "some eat", tu biberons "you bottle") phrases. In Experiment 1 ( N  = 59), the lists involved common nouns and verbs, while in Experiment 2 ( N  = 28), only common verbs were used. Eleven‐month‐olds showed a clear preference for correct over incorrect co‐occurrences in both experiments, while 8‐month‐olds showed a trend in the same direction. These results suggest that before their first birthday, infants' storage and access of words and word sequences are sufficiently sophisticated to include the means to track categorical dependencies. This early sensitivity to co‐occurrence patterns may be greatly beneficial for constraining lexical access and later on for learning novel words' syntactic and semantic properties.